2003
DOI: 10.1086/367711
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Virulence Gene,hylEfm, Predominates inEnterococcus faeciumof Clinical Origin

Abstract: An open reading frame (hyl(Efm)) with homologies to previously described hyaluronidase genes has been identified in nonstool isolates of Enterococcus faecium. E. faecium isolates (n=577) from diverse sources were screened for the presence of hyl(Efm) and esp(Efm), a putative virulence gene associated with epidemic E. faecium strains. The presence of esp(Efm) was roughly twice that of hyl(Efm), but both were found primarily in vancomycin-resistant E. faecium isolates in nonstool cultures obtained from patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
197
3
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(229 citation statements)
references
References 15 publications
12
197
3
17
Order By: Relevance
“…Wıth regard to the presence of the hyl virulence gene area, the rate of hyl was 4%-7% in European countries (8,24,34,35), 17.2%-100% in continental America (27,36,37), and 53% in Saudi Arabia (38) in VSE strains. We found that 12.9% of all isolates had the hyl gene in this study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Wıth regard to the presence of the hyl virulence gene area, the rate of hyl was 4%-7% in European countries (8,24,34,35), 17.2%-100% in continental America (27,36,37), and 53% in Saudi Arabia (38) in VSE strains. We found that 12.9% of all isolates had the hyl gene in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Although esp is common in E. faecalis isolates, it is more common in hospital-acquired E. faecium isolates in particular (4). The rate of esp expression in enterococcal isolates is 49.5%-77% (21)(22)(23) in Asian countries, 33%-65% (8,24,25) in European countries, and 33%-76% in continental America (26)(27)(28). A study (29) conducted in Turkey reported that this rate was 25.6%.…”
Section: Discussionmentioning
confidence: 99%
“…The hyl genes have shown to increase lethality in murine peritonitis model and according to Rice et al, (2003) this gene is never present in community associated clade. The hyl efm gene is predominantly seen in Vancomycin and Ampicillin resistant strains which come under hospital associated clade.…”
Section: Phenotypic Assessment Of Safety Of the Strain Enterococcus Fmentioning
confidence: 99%
“…The esp gene has an important role in biofilm formation of E. faecium (Heikens et al, 2007) and has been experimentally proven to contribute to endocarditis (Heikens et al, 2011) and urinary tract infections (Leendertse et al, 2009) in animal models. The esp gene is common among ampicillin and vancomycin resistant E. faecium isolates (Rice et al, 2003;Vankerchoven et al, 2004).…”
Section: Esp (Pathogenicity Island (Pai) Marker)mentioning
confidence: 99%